Single and combined impacts of irradiation and surgery on lymphatic vasculature and fibrosis associated to secondary lymphedema - Buntinx, F.; Lebeau, A.; Gillot, L.; Baudin, L.; Ndong Penda, R.; Morfoisse, F.; Lallemand, F.; Vottero, G.; Nizet, C.; Nizet, J. L.; Blacher, S.; Noel, A. (Frontiers in Pharmacology, 2022)
Lymphedema (LD) refers to a condition of lymphatic dysfunction associated with excessive fluid accumulation, fibroadipose tissue deposition and lymph swelling. In industrialized countries, LD development mainly results from a local disruption of the lymphatic network by an infection or cancer-related surgery (secondary LD). In the absence of efficient therapy, animal models are needed to decipher the cellular and molecular mechanisms underlying LD and test putative drugs. In this study, we characterized a murine model of lymphedema that combines an irradiation of the mice hind limb and a radical surgery (lymph node resection associated to lymphatic vessel ligation). We investigated the respective pathogenic roles of irradiation and surgery in LD formation by comparing their impacts, alone or in combination (with different intervention sequences), on different features of the pathology: swelling (paw thickness), lymphatic vasculature remodeling, epidermal/dermal thickening and fibrosis. This study supports the importance of radiation prior to surgery to rapidly induce a severe and sustained tissue remodeling harboring the different hallmarks of LD. Through a computerized method of digital image quantification, we established the spatial map of lymphatic expansion and matrix deposition in papillary and reticular dermis. We provide the first experimental evidence for an excessive deposition of periostin (POSTN) and tenascin-C (TNC) in LD. This mouse model is available to study the patho-physiology of LD and test potential therapeutic targets.